(untitled) (The Pakistan Development Review, 1993)
Almost all the World Fertility Surveys (WFS), and those repeating a similar pattern of pregnancy history data collection, like the Population, Labour Force, and Migration Survey (PLM) carried out in Pakistan in 1979-80, covered information on proximate determinants for the last closed and open birth intervals. This paper, based on the PLM data, discusses the methodological issue of data collection. The types of restriction used have often been doubted as they have produced biased estimates of contraceptive use and duration of breast-feeding, which are important in the estimation of birth interval and in the ultimate estimation of the structures of the relationship predicting fertility. The representativeness of the last closed and open birth intervals is limited if these are probed deeper in the time before survey, as the proportion of births gets quite small. It is inappropriate to estimate proximate determinants on fertility data that do not provide information on all the births. Therefore, an attempt has been made to estimate contraceptive use and breast-feeding with and without the WFS restrictions. The logit model has been used with a dichotomous variable, ’whether the next live birth occurs or not’, on proximate determinants and other socio-economic variables to estimate the amount of biasedness. The results reveal that there appears to be a higher proportion of unbiased estimates if they are derived through the unrestricted sample; and these results are in conformity with the results found elsewhere. The biasedness of the restricted samples also affects the studies aimed at observing the relationship between the predictor and the dependent variables.